Dental caries, fluorosis, and oral health behavior of children from Herat, Afghanistan. Issue 6 (18th June 2015) - Schwendicke, Falk; Doost, Ferhat; Hopfenmüller, Werner; Meyer‐Lueckel, Hendrik; Paris, Sebastian
Abstract Objective Decades of conflict, poverty, and dysfunctional public services have affected people's health in Afghanistan. To estimate treatment needs and guide health initiatives, epidemiologic data are required. Such data are currently unavailable for dental health. The present study assessed caries experience, fluorosis, and oral health behavior in children from Afghanistan. Methods We performed a two‐stage, school‐based cross‐sectional study in Herat province in Afghanistan. A total of 1059 children, 369 children aged 6–7, 300 aged 12, and 390 aged 15 years, were sampled. Caries was assessed according to ICDAS, and oral hygiene, dietary habits, and parental economic and educational status evaluated. Prevalence of fluorosis was assessed, and fluoride concentrations in drinking water and in used toothpastes were measured. Results Mean (SD) number of decayed, missing, or filled teeth was dmft = 4.88 (3.11), DMFT = 2.57 (2.16), and DMFT = 4.04 (3.03) in 6‐/7‐, 12‐, and 15‐year‐olds, respectively. The majority of lesions in 6‐year‐olds were cavitated, while 12‐ and 15‐year‐olds showed more non‐ or microcavitated lesions. Most lesions, especially in young children, were untreated. Mean (range) water fluoride concentration was 0.37 (0.19–0.67) ppm. Fluoride concentrations in evaluated toothpastes did not meet internationally recommended levels. The majority of children showed no or minimal fluorosis. Having fluorosis, infrequently consuming sweets, or having a father with high education was associated with low caries experience (dmfs/DMFS < 10), with OR (95% CI) being 0.64 (0.47/0.90), 0.65 (0.44–0.95), and 0.64 (0.47/0.90), respectively. Conclusions Examined Afghan children had high unmet dental treatment needs and caries experience. Sufficient access to restorative treatment and prevention measures is urgently required.